Analysis of socio-economic factors and vulnerability of fishermen and female fish traders to HIV/AIDS in fishing camps in the Kasenga-Luapula-Moero region, Katanga Province, Democratic Republic of Congo: final report - Hâ¿sken, S. M. C.
This report present the matrix and foundation of the study conducted in Katanga, based on the assumption that communities of fishermen in the Kasenga û Luapula û Moero area are vulnerable to HIV/AIDS due to a mix of several socio-economic factors and the presence of female fish traders in the fishing areas (fishing camps). The present study targeted all the fishing areas extending from Kasenga city through Luapula River to Lake Moero The present study seeks to identify socio-economic factors which are the root causes of the vulnerability of fishermen and female fish traders to HIV/AIDS in the fishing camps. From this perspective, an appropriate intervention will be developed and applied to the Kasenga û Luapula û Moero region with a view to reducing vulnerability factors to HIV/AIDS. Finally, the research team will make recommendations on the implementation of a pilot project geared towards protecting female fish traders and improving their living conditions with regard to their health and business.Nutritive value, Socioeconomic aspects, Fisheries, Research, AIDS